AB1089 Investigation of the efficacy and safety of secukinumab treatment in juvenile idiopathic arthritis subtypes of juvenile psoriatic and enthesitis-related arthritis: design of a randomised, double-blind, placebo controlled, multicenter study. (12th June 2018) - Foell, D.; Veit, J.A.; Ilsley, E.; Abrams, K.; ,
Abstract : Background: Secukinumab (AIN457), a fully human anti-interleukin-17A monoclonal antibody, has demonstrated a significant clinically meaningful efficacy on signs and symptoms, structure and function in adults with ankylosing spondylitis (AS) 1 and psoriatic arthritis (PsA) 2, both approved indications. These data support the proposed study in children with enthesitis-related arthritis (ERA) and juvenile psoriatic arthritis (JPsA). Objectives: This phase 3 study will investigate the efficacy and safety of secukinumab in children≥2 to<18 years with active JPsA or ERA. The primary objective is to demonstrate that the time to flare in a double-blind placebo control treatment withdrawal part of the trial is longer with secukinumab than placebo. Methods: Eighty biologic-naïve children with active ERA or JPsA (active:≥3 active joints and >1 site of enthesitis at baseline or documented by history) will enrol into treatment period 1 and receive weekly open label s.c. secukinumab 75 or 150 mg, based on their body weight (<50 kg or ≥50 kg) to maintain secukinumab blood levels equivalent to the adult 150 mg dose, for the first month then every 4 weeks thereafter. At week 12, responders (minimum JIA ACR Pedi 30 response) enter treatment period 2 and will be randomised to receive secukinumab or a matching placebo every 4 weeks. Patients enter treatment period 3 if they experience a disease flare or when the treatment period 2 closes for the entire study because the target number of flares has been reached. Upon entering treatment period 3, patients receive open-label secukinumab every 4 weeks until week 100 and then followed until week 112. Results: The primary efficacy endpoint will be time to flare in treatment period 2. Key secondary endpoints include JIA Pedi ACR 30/50/70/90/100 response rate, total dactylitis and enthesitis counts at week 12. Safety and tolerability will be assessed throughout the study. Conclusions: The efficacy of Secukinumab in the approved adult indications of PsA and AS support the current study design to evaluate the efficacy and safety of secukinumab treatment in children with active JPsA or ERA. The primary efficacy endpoint will be time to flare in treatment period 2. Key secondary endpoints include JIA Pedi ACR 30/50/70/90/100 response rate, total dactylitis and enthesitis counts at week 12. Safety and tolerability will be assessed throughout the study. References: [1] Baeten D, et al. Lancet. 2013;382(9906):1705–13 [] 2McInnes IB, et al. Lancet. 2015;386(9999):1137–46 Acknowledgements: This research was funded by Novartis Pharma AG, Basel, Switzerland Disclosure of Interest: D. Foell Consultant for: Novartis Pharma GmbH, Speakers bureau: Novartis Pharma GmbH, J. Veit Employee of: Novartis Pharma GmbH, E. Ilsley Employee of: Novartis Pharma AG, K. Abrams Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation